Makers of modern strategy : from Machiavelli to the nuclear age - Paret, Peter; Craig, Gordon Alexander, 1913-2005; Gilbert, Felix, 1905-1991 (Princeton paperbacks., 1986)
This text discusses Machiavelli, Maurice of Nassau, Gustavus Adolphus, Raimondo Montecuccoli, Vauban, Frederick the Great, Guibert, Bulow, Napoleon, Jomini, Clausewitz, Adam Smith, Alexander Hamilton, Friedrich List, Engels, Marx, Moltke, Schlieffen, Delbruck, Bugeaud, Gallieni, Lyautey, Alfred Thayer Mahan, Liddell Hart, De Gaulle, and other military strategists.